Synthesis of (–)-Phaitanthrin D and (+)-Dihydropyrroloindoloquinazolinone - Vaidya, Sagar D.; Argade, Narshinha P. (Synthesis, 2016)
The synthesis of (–)-phaitanthrin D and (+)-dihydropyrroloindoloquinazolinone are reported starting from the corresponding especially designed enantiomerically pure pivotal anthranilamide based building blocks using HMDS/ZnCl2 and NaHMDS.
Keywords: natural products; intramolecular reactions; stereoselectivity; cyclizations; lactonizations; lactamizations